Peran gen Z dalam pemerintahan demokrasi di Indonesia kedepannya - Putri, Hanifah Salsabila Wahyu (Maliki Interdisciplinary Journal, 2026)
This article aims to discuss about the crucial role of Gen Z in the government democracy system in Indonesia, this article will contain information about the challenges that they will face, characteristic and behaviour that they need to posses as well as the strategy that they can use to lead the government upfront when their time comes. In this article, it is highlighted that the implementation of the democracy system in Indonesia might still not be fully well implemented. In this article too will be explained about how Gen Z as a Post-Social media generation have a unique potential in regards to solving the problems above, this is because due to their early exposure to social media, they can be more adaptable in handling as well as making a solution for it. But that doesn’t mean that Gen Z is not without it’s inferiority. Experience is something that Gen Z couldn’t win and currently don’t have, therefore it might be a good idea for the senior generation to guide these youngster for them to be ready to be the face of the government in the future.